Synthesis and Characterization of Some Complexes of Cr(II) with 3-Cyano-2(1H)-pyridone Derivatives as Ligands - HAGHGOOIE, HOSSEIN; TABRIZI, LIELA; NOURI, SIROUS (Asian Journal of Chemistry, 2010)
By reaction of acetates of Cr(II) [Cr2(O2CCH3)4·2H2O] with the sodium salt of 3-cyano-2(1H)-pyridone derivatives, the dimeric compounds of Cr2(L)4·H2O, (L = 3-cyano-6-methyl-; 3-cyano-4,6-dimethyl-; 3-cyano-5,6-dimethyl-;3-cyano-6-isopropyl-; 3-cyano-6-phenyl-2(1H)-pyridone) have been synthesized. These complexes have been characterized by elemental analysis, FTIR, 1H NMR, UV-Vis spectra and atomic absorption spectrometer and have been ascertained that the nitrogen atom of the cyano group remain without coordinated. In all complexes, anion 3-cyano-2(1H)-pyridone derivatives act as 1,3-bridging ligands. The stability of all five complexes is remarkably high. These complexes appear to be stable toward dry air at 25ºC indefinitely, but exposure to moisture-saturated air causes a slight greenish ting to appear after ca. 10 d.